Gaya Kepemimpinan, Iklim Organisasi, Kompensasi dan Kedisiplinan Guru - Muchsin Zuhad Al'asqolaini (Jurnal Manajemen dan Bisnis, 2021)
The purpose of this study was to determine the Impact of Leadership Style, Organizational Climate, and Compensation on the Discipline of Teachers in Mamba'ul Ihsan Ujungpangkah Gresik while partially and also simultaneously. Quantitative methods is used in this research with a 38 total population and also as sample. Saturated sampling techniques is used for method. The analysis in this research includes: validity test, reliability test, classic assumption test, multiple linear regression analysis, coefficient of determination analysis (R²), t test and F test. The results of multiple linear regression analysis obtained by the regression equation Y = 1.140 + 0.202X1 + 0.641X2 + 0.269X3 + e. To find out the strength of the relationship between variable X and Y, a statistical calculation using the correlation coefficient formula is obtained R Square = 0.627. This shows that all variable are have a strong relationship. The statistical test found that partially the influence of leadership style on teacher discipline obtained a figure of 2,078. and than organizational climate on the discipline of teachers obtained a figure of 5,191. The effect of compensation on the discipline of teachers obtained a figure of 2,857. the leadership style, organizational climate, and compensation simultaneously had a significant impact on discipline, this can be seen from the calculated F value of 19.072.